Government and the Railways in Nineteenth-Century Britain - Parris, Henry (Heritage, 2019)
Railways presented nineteenth century governments with political as well as economic problems: their inherently monopolistic tendencies were recognized almost from the start. Hence the widely accepted notions of laissez-faire did not apply. The book traces government regulation of British railways from its beginnings in 1840. Based on departmental records, the private papers of politicians and administrators, and the archives of the companies themselves, it shows how far state intervention could go even in an age of individualism. For the student of government, it throws new light on the process of administrative decision-making, the sources of legislation and the workings of interest groups. Historians will find accounts of the origin of administrative law and the working of the civil service in the last days of patronage. For those interested primarily in railways, the book shows the influence of government on the development of such devices as interlocking signals, block working and continuous brakes